2019
DOI: 10.1002/smtd.201900179
|View full text |Cite
|
Sign up to set email alerts
|

Coassembly of Complementary Peptide Nucleic Acid into Crystalline Structures by Microfluidics

Abstract: The self‐assembly of simple units into well‐ordered supramolecular polymeric structures may give rise to a broad range of desirable attributes. In the field of bionanotechnology, there are two main classes commonly used as building blocks for self‐assembly—amino acids and nucleobases. While protein, peptide, and amino acid building blocks propose broad chemical versatility, the specific Watson–Crick base pairings of nucleic acids allow rational design and precise control over the assembly process. Specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…It was shown that single amino acids in their aggregated form can also produce a fluorescent signal, which is not evident in the monomeric state (Babar and Sarkar, 2017;Banerjee et al, 2020;Niyangoda et al, 2017;Shaham-Niv et al, 2018). Numerous observations suggest that the optical phenomenon of aggregation-induced intrinsic fluorescence is broader than originally speculated, as it also applies to many other metabolites and nucleic acids (Arnon et al, 2019;Berger et al, 2015;Chen et al, 2018;Lakowicz et al, 2001;Stephens et al, 2020;Zou et al, 2002). Circumstantial evidence and argumentation suggested that supramolecular packing is important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that single amino acids in their aggregated form can also produce a fluorescent signal, which is not evident in the monomeric state (Babar and Sarkar, 2017;Banerjee et al, 2020;Niyangoda et al, 2017;Shaham-Niv et al, 2018). Numerous observations suggest that the optical phenomenon of aggregation-induced intrinsic fluorescence is broader than originally speculated, as it also applies to many other metabolites and nucleic acids (Arnon et al, 2019;Berger et al, 2015;Chen et al, 2018;Lakowicz et al, 2001;Stephens et al, 2020;Zou et al, 2002). Circumstantial evidence and argumentation suggested that supramolecular packing is important.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of aggregation-dependent luminescence of proteins is a rapidly evolving field ( Ardona et al., 2017 ; Arnon et al., 2019 ; Babar and Sarkar, 2017 ; Banerjee et al., 2020 ; Berger et al., 2015 ; Bhattacharya et al., 2017 ; Chan et al., 2013 ; Kong et al., 2019 ; Niyangoda et al., 2017 ; Pansieri et al., 2019 ; Pinotsi et al, 2013 , 2016 ; Prasad et al., 2017 ; Shaham-Niv et al., 2018 ). Protein aggregates were shown to absorb light at wavelengths above 300 nm and to exhibit a structure-specific fluorescence in the visible range, even in the absence of aromatic amino acids ( Del Mercato et al., 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such a behaviour of the fluorescence emission band is known as the red-edge excitation shift effect and is characteristic for the self-assembly induced fluorescence of amino acids, peptides and proteins. 16,17,27 The presence of elongated fibrillar structures was detectable by fluorescence lifetime imaging, without the use of any external dyes, only by using the autofluorescence signal of the sample (Figure 4c). The autofluorescence decay curve obtained for the phenylalanine fibrils, revealed the presence of 0.35 and 2.53 ns decay times after fitting to a biexponential model (Figure 4d).…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13] Numerous observations suggest that the optical phenomenon of aggregation induced intrinsic fluorescence is broader than originally speculated, as it also applies to many other metabolites and nucleic acids. [14][15][16][17][18][19] Circumstantial evidence and argumentation suggested that supramolecular packing is important. It was suggested that the hydrogen bonds and, in specific cases, the aromatic stacking, can underlie these optical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation